2021
DOI: 10.1177/0361198120986573
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Fatality and Injury Savings Because of Deployment of Advanced Wrong-Way Driving Countermeasures on a Toll Road Network

Abstract: Limited access facility wrong-way driving (WWD) crashes are typically more severe than other crashes. Deploying advanced WWD countermeasures, such as rectangular flashing beacon (RFB) and light-emitting diode (LED) technologies, at exit ramps can reduce WWD crashes, injuries, and fatalities. No previous research has developed a methodology to quantify the potential fatality and injury savings because of future countermeasure deployments. This paper developed such a methodology and applied it to Florida’s Turnp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Researchers in Tennessee evaluated three different WWD prevention systems based on accuracy, responsiveness, cost, and other criteria to identify the best system (9). The UCF authors have also done significant research on the effectiveness of RFB and LED countermeasures in reducing WWD on Florida toll road exit ramps, but these studies have mainly focused on turnaround rates and associated reductions in crashes, injuries, and fatalities (12,(22)(23)(24)(25). Researchers from Texas and Florida analyzed WWD events to evaluate the effects of WRONG WAY signage, pavement markings, and RFB and LED countermeasures; the results indicated that installing signs on the outside of wrong-way turns, using arrow markings on highway through lanes, and installing RFB or LED countermeasures could effectively deter wrong-way drivers (26).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers in Tennessee evaluated three different WWD prevention systems based on accuracy, responsiveness, cost, and other criteria to identify the best system (9). The UCF authors have also done significant research on the effectiveness of RFB and LED countermeasures in reducing WWD on Florida toll road exit ramps, but these studies have mainly focused on turnaround rates and associated reductions in crashes, injuries, and fatalities (12,(22)(23)(24)(25). Researchers from Texas and Florida analyzed WWD events to evaluate the effects of WRONG WAY signage, pavement markings, and RFB and LED countermeasures; the results indicated that installing signs on the outside of wrong-way turns, using arrow markings on highway through lanes, and installing RFB or LED countermeasures could effectively deter wrong-way drivers (26).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The collected data are invaluable in understanding traffic dynamics, identifying issues, and bringing forth practical solutions. Current approaches to traffic monitoring systems depend on traffic detector sensors, vehicular adhoc networks (VANETs) ( 3 ), or video processing for data collection ( 4 , 5 ). Traffic detector sensors such as roadside sensors, Bluetooth detection, or inductive loops usually capture basic traffic information such as speed, headway, or counts.…”
mentioning
confidence: 99%